EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN SISWA KELAS XII SMA NEGERI 1 MATARAMAN - Hasanah, Uswatul; Syarif, Edy; Korompis, Ferry Lourens S. (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This research aims to determine the effectiveness of using video learning media in the 12th-grade classrooms at SMAN 1 Mataraman. The method employed in this study is a qualitative approach, involving data collection and analysis of the learning process of students utilizing the available video media at the school. The results of the analysis indicate that learning with the use of video media significantly aids students in understanding the material provided by the teacher, enabling them to grasp the content more effectively. Despite some studies showing different results, this research concludes that the use of video media in education greatly assists students in comprehending the materials presented by the teacher.